Hakikat Perlindungan Hukum Hak Masyarakat Adat Dalam Sistem Agraria Nasional (Studi Kasus Di Propinsi Sulawesi Tengah) - Maisa Maisa (Maleo Law Journal, 2017)
This study analyzes and discovers the nature of legal protection of indigenous peoples' rights in the national agrarian law system. This research uses Normative Law research type and Empirical Law. Sources of data obtained from the primary data and secondary data as an analysis material obtained from respondents and informants. The results showed that the legal protection of the rights of indigenous peoples required a normative synchronization effort on all legal products so that it was not contradictory to the 1945 Constitution of the Republic of Indonesia and LoGA based on customary law. as the main norm in the formulation, enforcement and design of the national agrarian legal system. Research recommendation It is recommended that all legal products related to land tenure and ownership patterns that are contradictory to the 1945 Constitution and the LoGA are revoked and / or adjusted to customary laws that evolve in the dynamics of indigenous communities and are still valid and binding.Kata Kunci : Culture. Legal protection